Inorganic–organic hybrid zinc phosphites with fluorescence/phosphorescence dual emission performances. Issue 39 (1st October 2018) - Ni, Ai-Yun; Mu, Ying; Pan, Jie; Han, Song-De; Li, Jin-Hua; Wang, Guo-Ming
Abstract : A strategy to prepare room temperature fluorescence/phosphorescence dual emission materials is explored by coordinating N-containing organic chromophores to metal phosphite frameworks. Abstract : An innovative and feasible strategy has been explored to prepare stable and highly effective room temperature fluorescence/phosphorescence dual emission materials, in which N-containing organic aromatic structure-directing agents were coordinated to metal phosphite frameworks.